2001
DOI: 10.1086/318488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hand Cleansing with Antimicrobial Soap or Alcohol-Based Gel on Microbial Colonization of Artificial Fingernails Worn by Health Care Workers

Abstract: This study was undertaken to determine differences in microflora on the nails of health care workers (HCWs) wearing artificial nails compared with control HCWs with native nails and to assess the effect on these microflora of hand cleansing with antimicrobial soap or alcohol-based gel. Cultures were obtained from 21 HCWs wearing artificial nails and 20 control HCWs before and after using antimicrobial soap or alcohol-based gel. Before cleansing with soap, 86% of HCWs with artificial nails had a pathogen (gram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
2
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 32 publications
1
96
2
9
Order By: Relevance
“…4 Artificial fingernails and rings of healthcare workers have both been associated with higher bacterial colony counts on the hands. [5][6][7][8][9][10] In addition, bacterial colonization of the fingernails and hands of healthcare workers has been linked to the transmission of Pseudomonas aeruginosa, a common nosocomial pathogen among neonates. [11][12][13][14] Although evidence-based guidelines promoting handwashing and hand hygiene among healthcare workers are published and supported by several organizations, [15][16][17] there is considerable evidence that compliance with these measures is suboptimal.…”
mentioning
confidence: 99%
“…4 Artificial fingernails and rings of healthcare workers have both been associated with higher bacterial colony counts on the hands. [5][6][7][8][9][10] In addition, bacterial colonization of the fingernails and hands of healthcare workers has been linked to the transmission of Pseudomonas aeruginosa, a common nosocomial pathogen among neonates. [11][12][13][14] Although evidence-based guidelines promoting handwashing and hand hygiene among healthcare workers are published and supported by several organizations, [15][16][17] there is considerable evidence that compliance with these measures is suboptimal.…”
mentioning
confidence: 99%
“…Ring wearing increased the frequency of hand contamination with potential health care-associated pathogens. Wearing artificial acrylic fingernails can also result in hands remaining contaminated with pathogens after use of either soap or alcohol-based hand gel 154 and has been associated with outbreaks of infection 155 (see also Part I, Section 23.4).…”
Section: Defective Hand Cleansing Resulting In Hands Remaining Contamentioning
confidence: 99%
“…The study about the use of antimicrobial soap or gel alcohol in hand hygiene concluded that there is frequently a substantial number of pathogens in subungual spaces, even after careful hand washing, with the use of surgical brushes (16) .…”
Section: Resultsmentioning
confidence: 99%